A companion to Chinese archaeology (Chichester, West Sussex)
xxiii, 640 sayfa
Keywords: “A Companion to Chinese Archaeology is an unprecedented, new resource on the current state of archaeological research in one of the world’s oldest civilizations. It presents a collection of readings from leading archaeologists in China and elsewhere that provide diverse interpretations about social and economic organization during the Neolithic period and early Bronze Age“ --